2020
DOI: 10.1177/2325967120903290
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Disability Related to Hip Dysplasia Using Objective Measures of Physical Performance

Abstract: Background: Lower extremity physical performance measures (PPMs), which can objectively quantify functional ability, are an attractive adjuvant to patient-reported outcome (PRO) instruments. However, few tests have been validated for use in hip instability. Purpose: To evaluate 4 different PPMs for their ability to differentiate between young adults with hip dysplasia indicated for treatment with periacetabular osteotomy (PAO) and asymptomatic controls and to test inter- and intratest reliability and relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 36 publications
2
17
1
Order By: Relevance
“…Our between-days, test–retest reliability findings for performance-based tests are generally similar to reports among other patient populations [ 23 , 24 , 28 , 29 , 34 37 , 39 , 40 , 51 , 52 ]. For example, among adolescents and young adults with hip dysplasia and controls ( n = 34), Scott et al reported self-selected gait speed test–retest reliability over 10 timed meters of a 14-m course (ICC 2,1 = 0.93; 95%CI: 0.87-0.96), [ 23 ] similar to our 10mWT reliability results (ICC 3,k = 0.95; 95%CI: 0.90-0.97). Among children with neurological conditions, Graser et al also reported similar between-days reliability using 10-timed meters over a 14-m course (ICC 2,1 = 0.90; 95%CI: 0.80-0.95).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our between-days, test–retest reliability findings for performance-based tests are generally similar to reports among other patient populations [ 23 , 24 , 28 , 29 , 34 37 , 39 , 40 , 51 , 52 ]. For example, among adolescents and young adults with hip dysplasia and controls ( n = 34), Scott et al reported self-selected gait speed test–retest reliability over 10 timed meters of a 14-m course (ICC 2,1 = 0.93; 95%CI: 0.87-0.96), [ 23 ] similar to our 10mWT reliability results (ICC 3,k = 0.95; 95%CI: 0.90-0.97). Among children with neurological conditions, Graser et al also reported similar between-days reliability using 10-timed meters over a 14-m course (ICC 2,1 = 0.90; 95%CI: 0.80-0.95).…”
Section: Discussionsupporting
confidence: 88%
“…Among typically-developing children and young adults, ‘self-selected’ gait speeds for 11–30 year olds are, on average, 1.28–1.36 m/sec, [ 49 ] which is significantly faster than speeds obtained in our participants with AMC (i.e., 1.01–1.02 m/sec). Further, Scott et al found gait speeds of 1.2 ± 0.2 m/sec among adolescents and young adults with hip dysplasia ( n = 24), suggesting gait speeds with AMC, where multiple lower-limb regions are typically involved, are worse [ 23 ]. Collectively, results highlight the importance of evaluating and addressing reduced gait speed among individuals with AMC, particularly since ‘self-selected’ gait speed is better correlated to perceived gait quality when compared to other performance-based measures, like the 6-Minute Walk Test, in young adults with congenital, mobility-limiting conditions [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations